Business Ethics in the Greater China Region: Past, Present, and Future Research - Yin, Juelin (Journal of business ethics, 2018)
While business ethics has generated a great deal of research internationally over the last few decades, academic reviews of the business ethics literature remain limited. Moreover, there has been little attempt to date to analyze this literature specifically in the Greater China region, which has been experiencing rapid socioeconomic growth and dynamic evolution of business ethics in recent decades. This paper addresses this research gap by undertaking a comprehensive and critical appraisal of the business ethics literature on Greater China. In particular, it maps out the existing research findings, identifies limitations in methodology, and suggests future directions for business ethics research in this region. The findings indicate that the scholarly interests cover 24 research themes, including corporate social responsibility and social performance; ethical beliefs, judgment, values, decision-making, and culture; workplace ethics and behavior; marketing ethics and consumer behavior; and sustainability. This review reveals a growing imbalance between empirical and conceptual/theoretical studies on business ethics. In addition, the published works covered in this review heavily rely on survey method and convenience sampling, with a predominant focus on a single individual level of analysis. Importantly, this study identifies four directions for future research: contextualized theoretical development, addressing multilevel research, developing research design tailored to the Chinese context, and ensuring more diversified and rigorous data collection.